An investigation of emerging music courses in Colorado secondary schools - Cort, Madeleine Amy, author; Johnson, Erik, advisor; Grapes, K. Dawn, committee member; Decker, Derek, committee member (Colorado State University. Libraries, 2022)
Emerging Music Courses (EMCs) are music classes for secondary students outside of traditional ensemble offerings and include courses in composition, music theory, music technology, guitar, piano, and general music. These classes are a growing trend and serve as an access point to music learning for students who play an instrument not offered in ensembles, are not enrolled in traditional ensemble courses, or have musical interests outside of ensemble performance (Abril & Gault, 2008; Kubik, 2018; Sanderson, 2014; Veronee, 2017). Though these courses are popular choices for students (Pendergast & Robinson, 2020) and viable options for teachers looking to increase their course offerings (Freedman, 2019; Sanderson, 2014), music educators historically lack training in the pedagogical practices of these courses (Kubik, 2018; Ruthmann, 2006; Sanderson, 2014). Additionally, there is a lack of research surrounding the EMCs currently being offered by Colorado secondary schools and the practices of experienced EMC educators. The purpose of this study was to investigate the prevalence of EMCs in Colorado's secondary public schools, examine the learning activities currently used in EMCs, explore the beliefs teachers have about music learning in the context of EMCs, and assess the impact of the COVID-19 pandemic on these courses. Findings suggest that a variety of EMCs are offered in Colorado secondary schools, with general music, guitar, and piano as the top three most offered courses. Learning activities in EMCs appear to focus on performing, reading, and appreciating music, in addition to applying skills learned outside of the classroom. The COVID-19 Pandemic affected the enrollment in and availability of EMCs and, to a lesser extent, the instructional delivery of EMCs. Results from follow-up interviews suggest that educators believe EMCs are valuable to their professional goals and students, but more training and preparation is needed in order for teachers to feel confident in their curricular design and delivery.
Keywords: emerging music courses; secondary; general music; Colorado